Fracture mechanics 3 : applied quality control - Grous, Ammar; Wiley eBooks (London : ISTE : Wiley, 2013)
This third book of a 3-volume set on Fracture Mechanics adds a pragmatic and supportive character to the previous volumes by focusing on case studies using corrected exercises that teachers, students or engineers will find extremely useful. Due to the wide themes approached in this series, it can also be used to organize work in this field in a new way, as well as in the maintenance of industrial plants. Several cases of sampling plans and their applications in industry are presented, as well as several solved case studies on the main indicators of capability according to ISO/TS 16949.
Includes index.
John Wiley and Sons
Keywords: Quality control -- Statistical methods; fracture mechanics Mechanics; Pragmatics; Quality control -- Statistical methods; TECHNOLOGY & ENGINEERING -- Quality Control; Quality control -- Statistical methods; Electronic books